2013
DOI: 10.1111/cod.12118
|View full text |Cite
|
Sign up to set email alerts
|

Usage test with palladium‐coated earrings in patients with contact allergy to palladium and nickel

Abstract: There is a low risk of eczema in palladium-allergic and nickel-allergic individuals when they wear jewellery coated with pure palladium, but further studies are needed to determine whether palladium, when present in alloys, could cause allergic reactions. PdCl2 , like NiSO4 .6H2 O, shows variability in patch test reactivity over time. Furthermore, Na2 PdCl4 seems to be a more sensitive test substance than PdCl2 for the detection of palladium allergy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 26 publications
0
10
0
1
Order By: Relevance
“…Tillman et al. investigated the minimal elicitation concentration (MEC) in 40 Pd‐sensitized patients ; they found considerable variation in MEC, ranging from 0.035% to 3.5%. Unfortunately, in this study, concentrations between 1.0% and 3.5% were not investigated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Tillman et al. investigated the minimal elicitation concentration (MEC) in 40 Pd‐sensitized patients ; they found considerable variation in MEC, ranging from 0.035% to 3.5%. Unfortunately, in this study, concentrations between 1.0% and 3.5% were not investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In an earlier study, 0.3%, 1.0% and 3.0% Na 2 PdCl 4 were tested in 20 patients to evaluate the irritancy of the different test concentrations (51); 1 positive reaction was found for 1%, and 4 positive reactions for 3%. Tillman et al investigated the minimal elicitation concentration (MEC) in 40 Pd-sensitized patients (45); they found considerable variation in MEC, ranging from 0.035% to 3.5%. Unfortunately, in this study, concentrations between 1.0% and 3.5% were not investigated.…”
Section: Pd Sensitization Prevalence and Optimal Test Concentrationmentioning
confidence: 99%
See 2 more Smart Citations
“…This raises the question of whether contact sensitization alone is enough to cause granulomas, as the clinical relevance of palladium hypersensitivity remains uncertain. Tillman et al investigated the wearing of palladium‐coated earrings, and found no skin reactions in 40 subjects who showed positive patch tests to palladium . Another possibility is that palladium permeates through the skin, causing a foreign body reaction.…”
Section: Discussionmentioning
confidence: 99%